2018
DOI: 10.1016/bs.mcb.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and functional analysis of syndecans

Abstract: Syndecans comprise a major family of cell surface heparan sulfate proteoglycans (HSPGs). Syndecans are composed of sulfated glycosaminoglycans (GAGs), heparan sulfate (HS) or both HS and chondroitin sulfate (CS), attached covalently to core proteins. Syndecans regulate many cellular processes, such as adhesion, proliferation, and migration. Syndecans bind and regulate molecules primarily through their HS chains, but do not bind to all HS/heparin-binding molecules. Furthermore, mice ablated for the syndecan-1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Additional modifications occur at the cell surface or ECM through the action of 6-O-endo-sulfatases and/or the endoglycosidase heparanase. The controlled biosynthesis and post-synthetic modifications of HS chains provide an enormous potential of heterogeneity and structural variability of HS chains which accounts for a wide variety of HSPG interactions with regulatory proteins and, in turn, for their biological activities [12][13][14][15]43]. Several studies have demonstrated that there are cell and tissue-specific changes in the HS chain synthetic pathway in cancer cells and tissues in vitro and in vivo, thus suggesting a close involvement of HS chain biosynthetic machinery in carcinogenesis [30,44,45].…”
Section: Structural Features Biosynthesis and Enzymatic Modificatiomentioning
confidence: 99%
“…Additional modifications occur at the cell surface or ECM through the action of 6-O-endo-sulfatases and/or the endoglycosidase heparanase. The controlled biosynthesis and post-synthetic modifications of HS chains provide an enormous potential of heterogeneity and structural variability of HS chains which accounts for a wide variety of HSPG interactions with regulatory proteins and, in turn, for their biological activities [12][13][14][15]43]. Several studies have demonstrated that there are cell and tissue-specific changes in the HS chain synthetic pathway in cancer cells and tissues in vitro and in vivo, thus suggesting a close involvement of HS chain biosynthetic machinery in carcinogenesis [30,44,45].…”
Section: Structural Features Biosynthesis and Enzymatic Modificatiomentioning
confidence: 99%
“…Similarly, syndecan-4, which is mainly involved in cytoskeletal and membrane reorganization and formation of focal adhesions, inhibits cell migration and tumor activity [ 63 ]. Consistently, mRNA expression of syndecan-1 and syndecan-4 is significantly reduced in colon carcinoma cells [ 40 ]. However, in different types of cancers, syndecan-1 and syndecan-4 may present the opposite effect, promoting the tumor progression [ 64 , 65 ].…”
Section: Heparan Sulfate Proteoglycansmentioning
confidence: 81%
“…The syndecans regulate cell adhesion, migration, cytoskeleton organization, and gene expression through the binding of ECM molecules and soluble ligands [ 40 ]. Since cancer cells exhibit less adhesive and more migratory characteristics in comparison to normal cells, syndecans are candidate molecules to be differently regulated in cancer cells.…”
Section: Heparan Sulfate Proteoglycansmentioning
confidence: 99%
“…Cell-surface syndecans links the cytoskeleton to the interstitial matrix by means of heparan sulfate chains and is expressed on leukocytes and endothelial cells. Syndecans regulate many cellular processes, such as adhesion, proliferation, and migration, and are susceptible to shedding by proteinases, resulting in the release of ectodomains that can act as competitive inhibitors of their cell surface-linked counterparts 93 95 and modulate the onset of different pathological processes 96 98 . Considering the role of syndecan-1 in the endothelial glycocalyx, its degradation in the hemorrhagic process generated by HF3 in the mouse skin suggests the impairment of its functions with consequences related to glycocalyx permeability and mechanotransduction of fluid shear stress, as well as to leukocyte access to endothelial tissue.…”
Section: Discussionmentioning
confidence: 99%